Preschool appropriate practices environment, curriculum, and development - Beaty, Janice J. (Cengage, 2019)
"Aligned around ten learning centers in a preschool classroom, Preschool Appropriate Practices, 5th Edition is a must-have resource for preschool teachers creating the learning environment in their classroom. Easy to read and full of practical ideas, this text helps you learn how to act as a facilitator of preschoolers' self-directed learning by setting up centers in the classroom. Creative ideas for involving children in all aspects of their learning, including rule making and curriculum planning, are found throughout. You'll also find many learning activities, including some incorporating children's books. Activities are based on the National Association for the Education of Young Children's (NAEYC) developmentally appropriate practice (DAP), a nationally recommended set of early childhood practices. Chapter summaries pull out key ideas that can be easily implemented in the classroom."--Provided by publisher.